Exploring immersive experience in journalism. (August 2018) - Shin, Donghee; Biocca, Frank
Although virtual reality (VR) has been widely used to deliver news stories in immersive journalism (IJ), it is not clear how people are actually experiencing these stories and their contexts. Focusing on the immersion feature of VR stories, this study explicates the user experience to determine what it is like to experience news stories in VR and how immersion improves viewing experiences in IJ. This study proposes a VR experience model in the IJ context that integrates cognitive, affective, and behavioral factors as the primary influencing determinants. The results indicate that the meaning of immersion strongly depends on the users' traits and contexts and that the function of immersion is strongly determined by the users' own cognition and intentions. VR stories are viewed and accepted based on the manner that users imagine and intend to experience them. The model demonstrates the users' cognitive processes of experiencing quality, value, and satisfaction, which determine how people empathize with and embody VR stories. The results confirm the relationship between immersion and both empathy and embodiment, implying a new conceptualization of immersion in the IJ context.